Perception of Pulmonary TB Patients on Treatment with Directly Observed Treatment Shortcouse (DOTS) Strategy in the UPTD Area of Serbelawan Puskesmas Simalungun Regency - Romauli Pakpahan (Institute of Computer Science (IOCS), 2022)
Pulmonary tuberclosis is an infectious disease which is still a major health problem and needs to be treated intensively in developing countries including Indonesia. To overcome this problem, since 1995 Indonesia adopted the Directly Observed Treatment Shortcourse (DOTS) strategy recommended by WHO and this strategy is deemed quite effective. This research was conducted in the work area of ​​the UPTD Puskesmas Serbelawan, Simalungun Regency by using a descriptive design as research. This study aims to identify the perceptions of pulmonary TB sufferers towards treatment with the Directly Observed Treatment Shortcourse (DOTS) strategy at the UPTD Puskesmas Serbelawan, Simalungun Regency. The population in this study were pulmonary TB patients who were being treated at UPTD Puskesmas Serbelawan. The number of samples studied was 40 people using total sampling technique. Data collection was done by using a questionnaire consisting of demographic data and perceptions of the strategic Directly Observed Treatment Shortcourse (DOTS) as measured by a Likert scale. The results showed that pulmonary tuberculosis sufferers had a positive perception of treatment with the Directly Observed Treatment Shortcourse (DOTS) strategy, however, the participation of all parties is still needed to help cure pulmonary TB sufferers and minimize the chain of transmission of pulmonary tuberculosis and especially health workers / health center nurses. Serbelawan to always provide information and counseling about pulmonary tuberculosis.